Mean Size as a Unit of Visual Working Memory. (July 2014) - Im, Hee Yeon; Chong, Sang Chul
Visual environments often contain multiple elements, some of which are similar to one another or spatially grouped together. In the current study we investigated how one can use perceptual groups in representing ensemble features of the groups. In experiment 1 we found that participants' performance improved when items were easily segmented by a grouping cue based on proximity, suggesting that spatial grouping facilitates extracting and remembering ensemble representations from visual arrays consisting of multiple elements. In experiment 2 we found that spatial grouping improved performance only when the grouped subsets were tested for the memory task, whereas it impaired performance when other subsets that were not grouped were tested, suggesting that the benefit from grouping may come from better extraction for storage, rather than later decision processes such as accessibility. Taken together, our results suggest that perceptual grouping of multiple items by proximity facilitates extraction of ensemble statistics from groups of items, enhancing visual memory of the ensembles in a visual array.